Advances in Hybrid Fabrication toward Hierarchical Tissue Constructs. Issue 11 (7th April 2020) - Dalton, Paul D.; Woodfield, Tim B. F.; Mironov, Vladimir; Groll, Jürgen
Abstract: The diversity of manufacturing processes used to fabricate 3D implants, scaffolds, and tissue constructs is continuously increasing. This growing number of different applicable fabrication technologies include electrospinning, melt electrowriting, volumetric‐, extrusion‐, and laser‐based bioprinting, the Kenzan method, and magnetic and acoustic levitational bioassembly, to name a few. Each of these fabrication technologies feature specific advantages and limitations, so that a combination of different approaches opens new and otherwise unreachable opportunities for the fabrication of hierarchical cell–material constructs. Ongoing challenges such as vascularization, limited volume, and repeatability of tissue constructs at the resolution required to mimic natural tissue is most likely greater than what one manufacturing technology can overcome. Therefore, the combination of at least two different manufacturing technologies is seen as a clear and necessary emerging trend, especially within biofabrication. This hybrid approach allows more complex mechanics and discrete biomimetic structures to address mechanotransduction and chemotactic/haptotactic cues. Pioneering milestone papers in hybrid fabrication for biomedical purposes are presented and recent trends toward future manufacturing platforms are analyzed. Abstract : There is a growing number of fabrication technologies available, including those based on additive manufacturing principles. Each technology has specific advantages and limitations, and combining them can open new opportunities for the fabrication of complex, hierarchical constructs. Milestone papers in hybrid fabrication for biomedical purposes are identified and trends toward future hybrid biomanufacturing platforms are analyzed.